Molecular Docking of Active Compounds of Syzygium myrtifolium Walp. Leaves on Leukotriene A4 Hydrolase Receptors as Colorectal Anticancer - Daini Amanah; Munawarohthus Sholikha; Vilya Syafriana; Yasman Yasman; Rosario Trijuliamos Manalu (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Active compounds found in Syzygium myrtifolium Walp. leaves such as flavonoids, phenolics, and betulinic acid are known to have pharmacological activities. This research aimed to find active compounds found in Syzygium myrtifolium Walp. leaves, which have anticancer activity by inhibiting the protein leukotriene A4 hydrolase. Molecular docking methods are used to predict the activity and affinity between ligand-proteins. The research was conducted in silico on the active compound in Syzygium myrtifolium Walp. leaves, which met the five criteria of Lipinski’s rule for leukotriene A4 hydrolase with PDB code 3U9W. The software used were YASARA, MarvinSketch, and PLANTS, which can optimize ligands and bind ligand molecules to receptors. Then it was visualized using Discovery Studio Visualizer and analyzed the prediction of pharmacokinetics and toxicity. Docking results show that the four active compounds from the leaves of Syzygium myrtifolium Walp., namely bis (2-ethylhexyl) hexanedioate, 3-octadecyne, 1- octadecene, and (2E,6E)-farnesol have a lower docking score compared to bestatin; therefore, these four compounds have the potential to inhibit leukotriene A4 hydrolase receptors and can be candidates for colorectal anticancer compounds.